Tackling the crime of aggravated assault by the Criminal Investigation Unit of the Baubau Police Station - Zubair; La Ode Indra Maulid Awal Masirun; La Ode Muhammad Karim; Eko Satria; Al Hiday Nur (AIQU: Journal Multidiscipliner of Science, 2024)
Various acts of persecution that often occur in Baubau City, especially serious persecution, are a big task for law enforcement officials of Baubau Police in overcoming them. the problem that will be used as a source of reference to be researched is how to overcome the crime of serious persecution by Baubau Police satreskrim and its inhibiting factors. This type of research is normative empirical with primary and secondary data types and will then be analysed using descriptive qualitative. based on the results of the study it was found that the handling of cases experienced fluctuations in the number where there was a significant increase in the last year. The conclusion is that the process of overcoming crimes of serious maltreatment committed by the Baubau resort criminal police unit in the jurisdiction of the Baubau resort police must build a pattern of cooperation with other agencies in order to overcome the obstacles experienced in overcoming crimes of serious maltreatment influenced by the lack of personnel members of the Criminal Investigation Unit infrastructure facilities, and community culture